Versatile chemistry of six-membered NHC with boranes: bromination at sp(3) borane, activation of the B-H bond of HBpin, and ring expansion of NHC - Kundu, Gargi; Dixit, Ruchi; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2022)
The NHC.borane chemistry has been majorly restricted to imidazol-2-ylidene classes of carbenes. In our previous communication, we reported the synthesis of 6-SIDipp center dot BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene] and its electrophilic substitution reaction with iodine. Here, we have shown selective bromination of a 6-SIDipp stabilized sp(3) B-H bond. Treatment of 1.2 equivalents of N-bromosuccinamide with 6-SIDipp center dot BH3 gives a mixture of mono- and disubstituted products 6-SIDipp center dot BH2Br (1) and 6-SIDipp center dot BHBr2 (2). However, the reactions with alkyl bromides or carbon tetrabromide resulted in 6-SIDipp center dot BH2Br (1) selectively. Exploration of the chemistry of 6-SIDipp with BHCl2 and 9-BBN (9-borabicyclo[3.3.1]nonane) led to mono-6-SIDipp adducts 3 and 6a. Furthermore, 6a undergoes ring expansion to afford a seven-membered product, 6b, under mild conditions. Unlike BHCl2 or 9-BBN, the B-H bond of HBpin undergoes oxidative addition upon reaction with 6-SIDipp, epitomizing the first example (7) of a B-H bond insertion at NHCs. The analogous reactivity with HBcat led to a tetra-hydropyrimidinium salt with B(cat)(2) as a counteranion (8).